Health, behaviour and growth performance of Charolais and Limousin bulls fattened on different types of flooring. (7th May 2019) - Magrin, L.; Gottardo, F.; Brscic, M.; Contiero, B.; Cozzi, G.
Abstract : Intensive fattening of late-maturing breeds on concrete or rubberized slatted floors is the prevalent beef production system in mainland Europe. The rationale behind this study is that specific beef breeds with different slaughter weights might have a diverse response to different flooring systems. The study aimed at assessing whether growth performance, health, behaviour and claw condition of two beef breeds, Charolais (CH ) and Limousine (LIM ), would be affected by their housing on concrete (CS ) or rubber-covered (RCS ) fully slatted floor. A total of 228 CH (116 on CS; 112 on RCS) and 115 LIM (57 on CS; 58 on RCS) were housed in four and two commercial farms, respectively, in groups of 9.0 ± 2.1 animals/pen with an average space allowance of 3.1 ± 0.2 m 2 . Draining gaps of CS and RCS pens were 16.9 ± 1.7% and 11.6 ± 1.2% of the total surface, respectively. Bulls of both breeds had similar initial body weight (429.4 ± 31.5 kg for CH; 369.6 ± 31.7 kg for LIM), and they were slaughtered when they reached suitable finishing. Charolais had a higher final body weight (BW ) than LIM (750.8 ± 8.6 v . 613.7 ± 10.9 kg; P < 0.01), and bulls of both breeds on RCS had higher average daily gain than on CS (1.47 ± 0.02 v . 1.39 ± 0.02 kg/day; P < 0.05). The percentage of bulls early culled or treated for locomotor disorders were reduced by RCS only for LIM, while RCS tended to prevent the occurrence of bursitis for both breeds. During two 8-h behavioural observations, bulls on RCS performed more head butt/displacements and chases than on CS, and they reduced the frequency of abnormal lying down events. The use of RCS increased mounts' frequency only in LIM, while its reduced drainage capacity impaired only the cleanliness of CH. Postmortem hoof inspection showed longer claw dorsal wall and diagonal lengths, and sharper toe angles for CH on RCS than LIM on both floors. Results of this study point out that fully slatted floors, regardless of being rubberized or not, are not suitable for bulls finished at a final BW above 700 kg due to their detrimental effects on health and welfare. The use of RCS could be recommended as an alternative to CS only if bulls are slaughtered at a lower final BW (around 600 kg), like in the case of LIM breed.